Identification of Religious and Cultural Elements in Arts Learning Materials at Indriyasana Somoitan Kindergarten and Mosque Syuhada Kindergarten - Joko Pamungkas; Adi Dieni Maulana Rizka (International Journal of Integrated Science and Technology, 2024)
This research aims to describe religious and cultural elements in art learning materials in kindergarten. Art learning in early childhood is often carried out to develop various aspects of intellectual, social and spiritual maturity. This can be supported by the school's background under a religious foundation so that the learning carried out can be adapted to the existence of a religious environment in each school. The two schools use different cultural and religious elements in art learning at school. The writing of this article is the result of observations, interviews and documentation carried out using qualitative research methods with triangulation of data sources. The data analysis carried out obtained the results that the religious elements that appeared in arts learning in the two kindergartens were religious stories, religious singing, prayer activities with tunes, projects through stories in books, dancing with religious songs, playing angklung with spiritual songs, and playing gamelan with religious songs such as prayers. Meanwhile, the cultural elements applied are the introduction of traditional musical instruments, the introduction of traditional dance, the singing of children's songs, the use of traditional games associated with learning, making batik, and the use of traditional clothing in art learning.